Planning as strategy for improving Black and Latinx student equity: Lessons from nine California community colleges - Felix, Eric R.; Castro, Marlon Fernandez (Education Policy Analysis Archives, 2018)
In 2014, California policymakers passed the Student Equity Plans (SEP) policy to address disparities in the community college system. The reform effort formalized a campus-wide planning effort that required institutions to examine their data for disparities, develop goals and strategies to mitigate identified inequities, and use new fiscal resources to realize their plans. In recent years, there has been an increase in the enactment of state-level higher education policies, but few, if any, have focused on the notion of equity or explicitly named racial and ethnic groups as policy beneficiaries. This study examines nine student equity plans in the state’s largest community college district. Drawing upon critical policy analysis, we place a focus on understanding if, and how, the planning process was used to address inequities facing Black and Latinx students. Based on our analysis we found several themes on how plans identified and address barriers facing Black and Latinx students. After examining 178 equity activities, we found only 28 promising activities that explicitly targeted Black and Latinx students with culturally relevant, data-driven, evidence-based strategies. These findings have compelling implications for policymakers seeking to develop reform efforts and institutions using policy to address current and historic inequities faced by Black and Latinx students. The use of planning for improvement is commonplace in educational policy, but we find that more training and capacity-building efforts are necessary to use planning as an opportunity to address racial inequity in community college.